1999
DOI: 10.1177/026461969901700306
|View full text |Cite
|
Sign up to set email alerts
|

Cheaper Can Be Better: Cutting Costs and Improving Low Vision Aid Service

Abstract: The traditional Low Vision Aid service using Hospital Eye Service Prescription forms is expensive and often associated with poor patient satisfaction as found in the studies by Mcllwaine, Bell and Dutton (1991) and by Humphrey and Thompson (1986). We audited this service in a district general hospital. Subsequently a more integrated "In House" Low Vision Aid clinic was established. The new service was re-audited to compare costs and also to look at patient satisfaction. The first audit composed a retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…18 The low vision aid cost was an assessment of hospital eye service prescription forms in a district general hospital. 19 Expert opinion has been used to estimate the proportion using low vision aids. 20 21 The cost of low vision rehabilitation is from a cost per care episode of a health authority community occupational therapist.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 The low vision aid cost was an assessment of hospital eye service prescription forms in a district general hospital. 19 Expert opinion has been used to estimate the proportion using low vision aids. 20 21 The cost of low vision rehabilitation is from a cost per care episode of a health authority community occupational therapist.…”
Section: Methodsmentioning
confidence: 99%
“…14 The low cost of low vision aids is from an audit of an ''in-house'' NHS hospital low vision aid service. 19 This was not taken as the standard cost as a recent survey has shown that only 32% of low vision aid services are of this type. 34 For the percentages of low vision aid provision, the estimate by Margrain is the more recent 21 but the RNIB report may be more accurate.…”
Section: Sensitivity Analysis Around Cost Of Rapidly Deteriorating VImentioning
confidence: 99%
“…In the early 1990s, when reports on the effectiveness of optometric low vision services in the UK were not encouraging, the services in Scandinavia were reporting improved effectiveness by incorporating a low vision therapist . This influenced some UK services to swap to a low vision therapy model of provision that incorporated a specially‐trained ‘low vision therapist’ …”
Section: The Development Of Services and Current Provisionmentioning
confidence: 99%
“…15,16 This influenced some UK services to swap to a low vision therapy model of provision that incorporated a specially-trained 'low vision therapist'. 17,18 A study in the UK 19 failed to measure any improvements in outcomes, when a 'low vision therapist' was incorporated into a service but another randomised controlled trial is now under way in America. 20…”
Section: Low Vision 'Therapy'mentioning
confidence: 99%